2008
DOI: 10.1016/j.jmarsys.2007.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in size at maturity of European hake Atlantic populations in relation with stock structure and environmental regimes

Abstract: European hake (Merluccius merluccius) female size at maturity is estimated on an annual basis for Bay of Biscay and Galician coast, which are parts of the distribution of the Northern and Southern stocks, respectively. Clear trends in this reproductive parameter are observed along the time series and the potential factors affecting these trends have been investigated. Total biomass, different indexes of SSB, age diversity index, fishing mortality at age, NAO winter index, upwelling index and temperature were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 82 publications
2
52
0
3
Order By: Relevance
“…Overexploitation due to excessive fishing effort (FAO, 2010) could have caused the decrease in L 50 observed for European hake. Moreover, the present first maturity sizes are lower than those recently reported in the northern Iberian Atlantic (Piñeiro and Sainza, 2003;Domínguez-Petit et al, 2008b). In our results, the L 50 for females (33.8 cm) is close to values reported for the Catalan Sea and northern Tyrrhenian Sea, estimated respectively at 35.8 cm and 35.1 cm (Recasens et al, 2008); these values are also slightly lower than those observed 10 years previously (Recasens et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Overexploitation due to excessive fishing effort (FAO, 2010) could have caused the decrease in L 50 observed for European hake. Moreover, the present first maturity sizes are lower than those recently reported in the northern Iberian Atlantic (Piñeiro and Sainza, 2003;Domínguez-Petit et al, 2008b). In our results, the L 50 for females (33.8 cm) is close to values reported for the Catalan Sea and northern Tyrrhenian Sea, estimated respectively at 35.8 cm and 35.1 cm (Recasens et al, 2008); these values are also slightly lower than those observed 10 years previously (Recasens et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
“…In the Mediterranean Sea, Bouhlal (1973) observed a maximum spawning peak in winter and two other Lahrizi (1996) northern Moroccan Atlantic 37.8 41.1 Length at which 50% of individuals are mature using a cumulative frequency Piñeiro and Sainza (2003) Iberian Spanish Atlantic 32.8 45.4 Length at which 50% of individuals are mature using a Logistic equation Domínguez-Petit et al (2008b) Iberian Atlantic -46.0 Logistic equation Domínguez-Petit et al (2008b) North Atlantic -41.0 Logistic equation Recasens et al (1998) Mediterranean Sea Gulf of Lions 28.8 38.0 Length at which 50% of the specimens have already matured at least once Recasens et al (2008) Catalan Length at which 50% of individuals are mature using a Logistic equation Recasens et al (2008) northern Tyrrhenian Sea -35.1 Length at which 50% of individuals are mature using a Logistic equation Bouaziz et al (1998) Region of Bou-Ismail (Alger) 21.5 30.6 Length at which 50% of individuals are mature calculated by the evolution of the percentage of mature specimens smaller peaks in spring and late summer in the Gulf of Tunis. In the Gulf of Lions a certain amount of interannual variability has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, garfish specimens analysed in this study were the smallest specimens ever collected and reported for comparable studies; observed differences between lengths at sexual maturity in divergent geographical areas suggest that this species is not resistant to environmental changes; hence, its reproductive parameters do not remain stable during unfavourable conditions (Domínguez-Petit et al 2008). Changes in maturity ogives could be associated with sample size and/or their level of exploitation as it is known that during a collapse of the population due to over exploitation, age at maturity diminished, whereas size at maturity increased slightly, probably as a compensatory response (Morales-Nin et al 2002;Engelhard and Heino 2004).…”
Section: Size At Maturitymentioning
confidence: 70%
“…De esta manera, las variaciones extremas (8.3 y 12,7 cm) observadas deben ser analizadas considerando otros factores no considerados aquí, tal como los cambios interanuales en el crecimiento (e.g., Grover 2005, CastilloJordán et al 2010) y que podrían determinar cambios en la talla de madurez. Se sugiere que futuros análisis consideren la evaluación de cambios simultáneos en la edad de madurez de la sardina común, única forma de saber si el crecimiento de las diferentes cohortes podría estar determinando cambios en la madurez de la sardina común en la zona centro-sur, o bien si se debe a los efectos del ambiente (e.g., Cardinale & Modin 1999, Dominguez-Petit et al 2008, o asincronía espacio-temporal en el ciclo reproductivo en la zona centro-sur.…”
Section: Resultsunclassified